Crimes against the right to information in the Kurdistan Region’s Right to Information Act No. 11 of 2013: Crimes against the right to information in the Kurdistan Region’s Right to Information Act No. 11 of 2013 - Yassen, Sabah (Humanities Journal of University of Zakho, 2023)
The right to information laws have a great importance within the legislative system for the great role played by the disclosure of information to the public, embodied in achieving a number of interests at the governmental and popular levels alike, represented in promoting the principles of good governance, human rights, exposing corruption and monitoring the performance of the government and the private sector in general, that required criminalizing attacks targeting the right to information, this is what the legislator in the Iraqi Kurdistan Region have made through the Right to Information Law No. 11 of 2013. Moreover, he failed in Drafting one of the criminal behaviours regarding the violation of the right to information, in addition to the fact that the violation of this right did not penalized of imprisonment, as stayed on fine that deters less than freedom-restricting penalties.